2015
DOI: 10.1002/jaba.218
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of the high‐probability instructional sequence with and without programmed reinforcement

Abstract: In 2 experiments, we examined the effects of programmed reinforcement for compliance with high-probability (high-p) instructions on compliance with low-probability (low-p) instructions. In Experiment 1, we compared the high-p sequence with and without programmed reinforcement (i.e., edible items) for compliance with high-p instructions. Results showed that the high-p sequence increased compliance with low-p instructions only when compliance with high-p instructions was followed by reinforcement. In Experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Of the five applications in which the high‐p sequence was efficacious in increasing low‐p compliance the delivery of an edible item (identified via a preference assessment), contingent upon compliance with each high‐p instruction, was necessary. These data are consistent with previous research (Wilder, Majdalany, Sturkie, & Smeltz, ), suggesting that the high‐p sequence is more efficacious when edible items, instead of praise, are delivered contingent upon compliance with high‐p instructions. In the current study, no separate assessment was conducted to determine participant preference for praise or the extent to which praise functioned as a reinforcer.…”
Section: Discussionsupporting
confidence: 91%
“…Of the five applications in which the high‐p sequence was efficacious in increasing low‐p compliance the delivery of an edible item (identified via a preference assessment), contingent upon compliance with each high‐p instruction, was necessary. These data are consistent with previous research (Wilder, Majdalany, Sturkie, & Smeltz, ), suggesting that the high‐p sequence is more efficacious when edible items, instead of praise, are delivered contingent upon compliance with high‐p instructions. In the current study, no separate assessment was conducted to determine participant preference for praise or the extent to which praise functioned as a reinforcer.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some authors have empirically examined the individual components that may be responsible for the effects of the high‐ p sequence (Normand, Kestner, & Jessel, ; Pitts & Dymond, ; Wilder, Majdalany, Sturkie, & Smeltz, ; Zuluaga & Normand, ). Generally, these studies suggest that a short inter‐instruction interval (Pitts & Dymond, ; Wilder et al, ), the delivery of preferred items for compliance with high‐ p instructions (Wilder et al, ; Zuluaga & Normand, ), and the presence of stimuli correlated with reinforcement for compliance with low‐ p instructions when delivering high‐ p instructions (Normand et al, ) are important components of the procedure. Interestingly, other studies in this general line of research suggest that the delivery of high‐ p instructions themselves may not be necessary to increase compliance (Bullock & Normand, ; Normand & Beaulieu, ).…”
Section: Introductionmentioning
confidence: 99%
“…In a replication of Zuluaga and Normand (), Pitts and Dymond () compared the effects of the high‐p sequence with programmed reinforcement (praise and edibles following compliance with high‐p instructions) and the high‐p sequence without programmed reinforcement (no praise or edibles following compliance with high‐p instructions) and found that compliance with low‐p instructions was greatest when programmed reinforcement was delivered contingent on compliance with high‐p instructions. Wilder et al () extended the findings of Pitts and Dymond by examining the effects of reinforcement quality following compliance with high‐p instructions. Specifically, the experimenters compared praise (a less preferred stimulus for the participants) with edibles (a more preferred stimulus for the participants) when reinforcing compliance with high‐p instructions.…”
mentioning
confidence: 99%
“…The high‐p sequence has been shown to be effective with a variety of populations, including participants ranging in age from preschoolers to adults, as well as individuals with various diagnoses (Lee, ). It has also been used to increase compliance with a variety of low‐p instruction categories, including academic instructions (Lee, Belfiore, Scheeler, Hua, & Smith, ), social instructions (Wilder, Majdalany, Sturkie, & Smeltz, ), instructions to increase food acceptance (Penrod, Gardella, & Fernand, ), and instructions related to medical tasks (Riviere, Becquet, Peltret, Facon, & Darcheville, ). Advantages of the high‐p sequence over other methods of increasing compliance are that it doesn't require physical guidance and has been socially validated in an early childhood setting (Jung, Sainato, & Davis, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation